2022
DOI: 10.1080/21655979.2022.2065945
|View full text |Cite
|
Sign up to set email alerts
|

β-Patchoulene represses hypoxia-induced proliferation and epithelial-mesenchymal transition of liver cancer cells

Abstract: Hepatocellular carcinoma (HCC) is a malignant tumor originating from liver epithelial cells with a high clinical mortality rate. β-Patchoulene (β-PAE) is a compound extracted from patchouli, which has analgesic, anti-inflammatory and antioxidant effects. This research aims to probe the impacts of β-PAE on hypoxia-induced HCC cell proliferation and epithelial-mesenchymal transition (EMT). Firstly, hypoxic injury models were constructed in HCC Huh-7 and MHCC97 cells, and the hypoxic injury cell models were then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…Research has demonstrated that both β-patchoulene and ginsenoside have anti-tumor properties. [31][32][33] These discoveries suggests that there may be potential clinical uses for shenmai injection. By leveraging these components, it may be possible to mitigate some of the undesirable side effects of radiotherapy and chemotherapy, thus improving the granulocytopenia caused by myelosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…Research has demonstrated that both β-patchoulene and ginsenoside have anti-tumor properties. [31][32][33] These discoveries suggests that there may be potential clinical uses for shenmai injection. By leveraging these components, it may be possible to mitigate some of the undesirable side effects of radiotherapy and chemotherapy, thus improving the granulocytopenia caused by myelosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…Decrease in N-cadherin and vimentin levels, and increase in E-cadherin levels can be observed after administration of β-elemene in inhibiting EMT in colorectal tumor [ 56 ]. As mentioned, hypoxia is involved in EMT induction and facilitated cancer invasion which can be overcome by β-patchoulene [ 57 ]. Moreover, there is a close association between EMT induction and drug resistance in human cancers [ 58 ].…”
Section: Emt Mechanism: General Aspects and Carcinogenic Functionmentioning
confidence: 99%
“…The hBMSCs were cultured in a-MEM medium (Gibco, Carlsbad, CA, USA) containing 10% fetal bovine serum (FBS, Gibco, USA), 100 U/ml penicillin and 100 mg/L streptomycins in 5% CO 2 at 37°C. 16 When reaching 70%-80% confluency, the cells were sub-cultured to the next generation using trypsin (Beyotime Biotechnology, Shanghai City, China), and hBMSCs of the 3rd-5th generation were used for subsequent experiments.…”
Section: Cell Culturementioning
confidence: 99%
“…For osteoblast differentiation, hBMSCs were cultured in 24-well plates using an osteogenic induction medium (a-MEM medium, 10% FBS, 50 mg/mL ascorbic acid, 0.1 mg/L dexamethasone, as well as 10 mmol/L b-glycerophosphate [Sigma-Aldrich, Louis, MO, USA]), for 8 days to induce them into osteoblasts. 16,17 For adipogenic differentiation, the cells were cultured in medium A (Cyagen, Guangdong, China) for 3 days and adipogenic differentiation medium B (Cyagen, Guangdong, China) for 1 day in turn. 16,17 Extraction and preparation of MOP…”
Section: Induction Of Osteoblast and Adipogenic Differentiationmentioning
confidence: 99%
See 1 more Smart Citation